Development of dietary fiber enriched sausage using rice bran - Sagar, MSR; Habib, M; Hashem, MA; Azad, MAK; Rahman, MM; Ali, MS (Meat Research, 2024)
The study was conducted to evaluate the effect of de oiled rice bran as a source of dietary fiber on the sensory, physicochemical and biochemical properties of chicken sausages. For this purpose, sausages were prepared into 4 different groups. They were as follows: control; broiler breast meat sausage without rice bran, broiler breast meat sausage with 5% rice bran, broiler breast meat sausage with 10% rice bran, broiler breast meat sausage with 15% rice bran. All parameters were analyzed at 0, 14th and 28th days of storage period. The surface color (CIE L*, a*, b*) of sausages samples were measured using a Minolta Chroma meter at different storage period. DM, Ash, Crude fiber, EE and pH showed significantly different among the different sausage batters. All the parameters except pH was significantly lower in control group compare to different rice bran sausage batter group. During the analysis of sausages, all proximate parameters were significantly different among different sausage treatment groups. DM, Ash and EE contents were significantly higher in rice bran groups compare to control, while CP content and pH were significantly higher in control group. DM and CP% increased, while EE% and pH decreased with increasing the storage period. The lightness (L*) value was higher, while redness (a*) and yellowness (b*) values were lower in control sausage compare to rice bran group sausages. Free fatty acid, TBARS were significantly lower in control group compare to rice bran sausages group. Peroxide value and TBARS value increased with increasing the storage period. In sensory analysis, significantly lower color, off-flavor, juiciness and tenderness were found in broiler breast meat sausage without rice bran. Although color, off- flavor, juiciness and tenderness were not varied during sensory evaluation, flavor and overall acceptability significantly differ among the four treatments. Sensory evaluation indicated higher acceptability of sausage with 5% rice bran incorporated group compare to other rice bran incorporated sausage group.